Analysis of Legal Solutions for Bankruptcy Companies Due to Cancellation of Homologation to Avoid Asset Settlement (Study in Indonesia) - Herdi Munte; Fridolin Siahaan; Song Tinus (Inovasi Pratama Internasional. Ltd, 2026)
Cancellation of homologationThe Debt Suspension of Payment (PKPU) process carries serious legal consequences for companies, namely the declaration of bankruptcy and the imposition of asset liquidation. In many cases, companies that actually still have economic potential are forced to lose all their assets due to rigid legal mechanisms with no room for improvement. This study aims to examine legal solutions so that companies experiencing bankruptcy due to the cancellation of homologation are not immediately liquidated, but can instead be given the opportunity for further restructuring. The method used is normative legal research with a statutory regulatory approach, case studies, and comparative law. The results show that the Indonesian legal system does not yet provide legal space for post-bankruptcy reorganization schemes, unlike systems in other countries such as the United States and Japan. This study recommends regulatory reform of the Bankruptcy Law to open up post-bankruptcy restructuring options and protection for companies that still have business prospects